Refugees' and Irregular Migrants' Self-Selection into Europe: Who Migrates Where? - Cevat Giray Aksoy; Panu Poutvaara (Center for Economic Studies and ifo Institute (CESifo), 2019)
About 1.4 million refugees and irregular migrants arrived in Europe in 2015 and 2016. We model how refugees and irregular migrants are self-selected. Using unique datasets from the International Organization for Migration and Gallup World Polls, we provide the first large-scale evidence on reasons to emigrate, and the self-selection and sorting of refugees and irregular migrants for multiple origin and destination countries. Refugees and female irregular migrants are positively self-selected with respect to education, while male irregular migrants are not. We also find that both male and female migrants from major conflict countries are positively self-selected in terms of their predicted income. For countries with minor or no conflict, migrant and non-migrant men do not differ in terms of their income distribution, while women who emigrate are positively self-selected. We also analyze how border controls affect destination country choice.
Keywords: J15; J24; O15; 330; refugees; self-selection; human capital; predicted income